Remodeling of HIV-1 Nef Structure by Src-Family Kinase Binding - Moroco, Jamie A. (J Mol Biol, 2017)
The HIV-1 accessory protein Nef controls multiple aspects of the viral life cycle and host immune response, making it an attractive therapeutic target. Previous X-ray crystal structures of Nef in complex with key host cell binding partners have shed light on protein-protein interactions critical to Nef function. Crystal structures of Nef in complex with either the SH3 or tandem SH3-SH2 domains of Src-family kinases reveal distinct dimer conformations of Nef. However, the existence of these Nef dimer complexes in solution has not been established. Here we used hydrogen exchange mass spectrometry (HX MS) to compare the solution conformation of Nef alone and in complexes with the SH3 or the SH3-SH2 domains of the Src-family kinase Hck. HX MS revealed that interaction with the Hck SH3 or tandem SH3-SH2 domains induces protection of the Nef αB-helix from deuterium uptake, consistent with a role for αB in dimer formation. HX MS analysis of a Nef mutant (position Asp123, a site buried in the Nef:SH3 dimer but surface-exposed in the Nef:SH3-SH2 complex), showed a Hck-induced conformational change in Nef relative to wild type Nef. These results support a model in which Src-family kinase binding induces conformational changes in Nef to expose residues critical for interaction with the μ1 subunit of AP-1 and the MHC-I tail, and subsequent MHC-I downregulation and immune escape of HIV-infected cells required for functional interactions with downstream binding partners.